2014
DOI: 10.2147/rmhp.s61473
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the benefit of health workforce secondment in Botswana: an approach for strengthening health systems in resource-limited settings

Abstract: To address health systems challenges in limited-resource settings, global health initiatives, particularly the President’s Emergency Plan for AIDS Relief, have seconded health workers to the public sector. Implementation considerations for secondment as a health workforce development strategy are not well documented. The purpose of this article is to present outcomes, best practices, and lessons learned from a President’s Emergency Plan for AIDS Relief-funded secondment program in Botswana. Outcomes are docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The capacity of the Zimbabwe government to fund healthcare has been eroded, leading to costs of healthcare services surpassing HCUs' capacity, especially at rural health facilities charging user fees. These findings were similar to those of another study conducted in Zimbabwe, 33 which showed that vacant positions for nurses at rural health facilities were frozen because of a lack of financial resources and that HCU fees were introduced despite HCUs not being able to afford to pay the fees.…”
Section: Outputssupporting
confidence: 89%
See 1 more Smart Citation
“…The capacity of the Zimbabwe government to fund healthcare has been eroded, leading to costs of healthcare services surpassing HCUs' capacity, especially at rural health facilities charging user fees. These findings were similar to those of another study conducted in Zimbabwe, 33 which showed that vacant positions for nurses at rural health facilities were frozen because of a lack of financial resources and that HCU fees were introduced despite HCUs not being able to afford to pay the fees.…”
Section: Outputssupporting
confidence: 89%
“…Material resources like medicines or drugs, medical accessories such as bandages, surgical blades and cotton wool, and medical equipment like microscopes are needed for the comprehensive provision of healthcare at health facilities. 33 The unavailability of these materials compromises the effective delivery of healthcare, as nurses (46.7%) cannot provide the healthcare and treatment needed by HCUs (59.95%). This then inevitably increases the disease burden in communities.…”
Section: Discussionmentioning
confidence: 99%
“…The kinds of health worker skills required to address HIV and AIDS are not unique when compared to the skills needed to address a broad range of other health issues. For instance, within the hospital setting, the same skills needed to ensure efficient administration of and adherence to HIV and AIDS treatment are the same types of skills required to deliver other types of health programs (Callaghan et al, 2010;Marseille et al, 2002;Semo et al, 2014). Investing in the human resources infrastructure needed to deliver HIV and AIDS related services, therefore, has the potential to lead to a health system's improved ability to more efficiently provide other services (Banati and Moatti, 2008;Callaghan et al, 2010;Hanefeld and Musheke, 2009;McCourt and Awases, 2007).…”
Section: Ownership and Health Systems Implications Of Hiv And Aids Ghismentioning
confidence: 99%
“…Secondments can therefore provide a positive way of motivating people and increasing work satisfaction, whilst enhancing best practice, collaborative working partnerships, knowledge and skills [ 70 ]. Although the practice of secondment is generally known as a strategy for skills development for mutual organisational and individual benefit, there is, however, a gap in the literature regarding practical implementation considerations and critical success factors related to the use of secondment as a global strategy to promote evidence-informed health policy development and implementation strategy [ 71 ]. This merits further consideration in future studies.…”
Section: Discussionmentioning
confidence: 99%